Design and develop a web-based information system for ordering and delivering goods at PT. Total Logistics - Aziz, Abdul; Bani, Alexius Ulan; Sharyanto, Sharyanto (Yayasan Bina Internusa Mabarindo, 2024)
The purpose of this research is to design and develop a Web-based information system for ordering and delivering goods at PT. Total Logistic. This system is designed to address issues in managing consumer complaints, where data received from customers through customer service is still managed manually, making it easy to get lost before moving on to the next process. Through an analysis of the current system, it was found that a web-based information system is needed to help address this issue and improve efficiency and customer satisfaction. This design utilizes a system development approach involving the creation of User Interface (UI) Design and Application Prototype. Testing of the developed UI and Prototype shows that the system functions well and has a valid success rate. With this web-based information system, PT. Total Logistic is expected to improve the quality of customer service and minimize the risk of data loss the delivering goods of consumer process.